Determination of some physical-chemical properties of biofortification soft wheat and flour of the varieties “Treska” - Marija Menkinoska; Vinko Stanoev; Valentina Pavlova; Tatijana Blazevska; Victorija Stamatovska; Natasa Gjorgovska (Journal of Engineering & Processing Management, 2017)
Cereal crops as a basic food for humans, little is used as a grain, but with millingthey are processed in the milling products: flour, meal, flakes and bran.Determining the content of some ingredients, such as protein, ash, wet gluten,fat, etc. in food products is important because they are present in the rawmaterials and final products. The importance of knowing the physical andchemical properties of wheat and flour is due to the determination of quality andkind of flour which is produced after milling process. The aim of this research isto examine the influence of Fe-EDTA fertilizers through soil, foliar and soil +foliarapplication on some physical and chemical properties of bio-fortification softwheat and flour of the varieties ,,Treska ,, During the investigation wedetermined the highest ash content in the seed obtained with soil + foliarapplication of iron, while in the flour was measured the highest ash content bysoil application of iron. We concluded that the supplement iron in soil increasethe percentage of protein in the grain and flour. We found that soil + foliarapplication of iron leads to a significant increase of % fat and wet gluten in grainand flour compared to soil or foliar application of chelating fertilizers. It might beconcluded that the agronomic bio-fortification with Fe-EDTA soil + foliarapplication and Fe-EDTA soil leads to improved examined physical - chemicalproperties of wheat and flour.
Keywords: Fe-EDTA soil foliar; physical-chemical properties; wheat and flour